Intellectual Property Rights in the Age of AI and Big Data: A Reinterpretation of the Concept of Creativity in Legal Philosophy - Pranajaya, I Kadek Widi; Kurniawan, I Gede Agus (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The legal issue addressed is the growing misalignment between traditional IPR doctrines—which require originality and human subjectivity—and the emerging reality of content creation that is either generated or significantly assisted by AI systems and data-driven processes. The primary objective of this research is to critically reassess the normative foundations of the concept of "creativity" within IPR law, employing a legal-philosophical approach, and to propose a more adaptive legal framework in response to technological advancements. The study adopts a normative juridical method combined with a progressive legal philosophy approach, and conducts a conceptual analysis of both international and national regulations concerning IPR, AI, and data governance. The novelty of this research lies in the formulation of the concept of hybrid creativity—an acknowledgment of non-anthropocentric forms of creative expression that possess expressive, aesthetic, and utilitarian value, even when generated through algorithmic intervention. The findings indicate that the exclusive recognition of human creativity is increasingly insufficient, and that a more inclusive legal paradigm is needed to accommodate the role of AI as a subject—or at least a co-creator—within the IPR system. The study recommends the establishment of a new category of IPR that recognizes AI-generated works, alongside a reformulation of originality and ownership criteria aligned with principles of distributive justice and technological progress